Property rights to land and its perception in rural part of central Albania - Edvin Zhllima; Davide Viaggi; Daniel Müller (New Medit, 2010)
The study makes an inquiry into the security of property (land) rights in Albania, making use of focus groups in a case study area of Albania. The paper addresses two types of subjective insecurity. First, we identified a subjective (perceived) insecurity of land owners resulting from the friction between the legal rights accepted by the majority and the ancestral rights of the former owners. Second, we investigated insecurity related to formal institutional failures regarding the enforcement of property rights. This insecurity regarding land rights affects land transactions; therefore, conducting research on the nature, causes and major factors related to this type of insecurity is of high relevance and importance for the agricultural sector in Albania.
Keywords: Q15; 330; land tenure; land reform; Albania